Ismail Mundu on Islamic Law of Inheritance: A Content Analysis of Majmū‘ al-Mīrāth fī Ḥukm al-Farā’iḍ - Hakim, Muhammad Lutfi (Al-Jami'ah Research Centre, 2023)
This article analyses a manuscript on the Islamic law of inheritance, entitled Majmū‘ al-Mīrāth fī Ḥukm al-Farā’iḍ, written by Ismail Mundu. The manuscript resulted from Mundu’s anxiety about the difficulties encountered by his students in understanding the Islamic inheritance-sharing mechanism and the predicted extinction of the Islamic law of inheritance. Through content analysis and historical approaches, the author found that the inclination of thought in Mundu’s Islamic law of inheritance was based on the Shāfi‘ī school with a clearly different point that constitutes its specific and evident contribution. The manuscript included charts containing concise formulas that were not in any other works of Shāfi‘ī school and that could be used as a practical guide to facilitate beginners in learning the Islamic law of inheritance. This article, therefore, contributes to the study of the history of Islamic law by providing evidence of the establishment of local ideas and thought on the Islamic law of inheritance applied by Mundu when he served as Mufti of the Kubu Kingdom and Judge of the Kubu Court from 1907 to 1957.[Artikel ini menganalisis sebuah manuskrip tentang hukum waris Islam, berjudul Majmū‘ al-Mīrāth fī Ḥukm al-Farā’iḍ, karya Ismail Mundu. Manuskrip ini disusun atas keprihatinan terhadap kesulitan-kesulitan yang dialami murid-murid Mundu dalam memahami mekanisme pembagian waris Islam dan ramalan kepunahan ilmu waris karena masyarakat Muslim lebih mengutamakan hukum adat. Melalui studi analisis isi dan pendekatan sejarah, penulis menemukan bahwa kecenderungan pemikiran hukum waris Islam Mundu berdasarkan pada mazhab Shāfi‘ī dengan perbedaan jelas yang merupakan kontribusinya yang spesifik dan nyata. Karya tersebut menyediakan jadwal (tabel) yang berisi rumus-rumus ringkas yang tidak terdapat dalam karya-karya mazhab Shāfi‘ī lainnya dan dapat digunakan sebagai pedoman untuk memudahkan para pemula dalam mempelajari hukum waris Islam. Oleh karena itu, artikel ini berkontribusi bagi kajian sejarah hukum Islam dengan memberikan bukti adanya gagasan dan pemikiran local tentang hukum waris Islam yang diterapkan oleh Mundu ketika menjabat sebagai Mufti Kerajaan Kubu dan Hakim Pengadilan Kubu (1907-1957).]